Croatian Concepts of Integration - Čepulo, Dalibor; Matković, Stjepan (The Development of European and Regional Integration Theories in Central European Countries, 2022)
The administrative fragmentation of historical and ethnic ʻCroatian lands’ in the Habsburg Monarchy and the insufficient political power of the Croats affected the formation of diverse Croatian national integration ideologies in the ʻlong 19th century’. The Yugoslav concept influenced the South Slavic unification in 1918, but experience with the unitary state under Serbian domination led to demands for an autonomous Croatian unit or independent state. The provisory Croatian autonomy of 1939–1941 and excessive fascist state between 1941–1945 were replaced by the autocratic crypto-centralist communist federation. The federation provided for constitutional autonomy of the republics and nations, but, in the end, endangered Croatia’s territorial integrity. The establishment of the Croatian state in 1991 was understood not only as a way out of this situation but also as an ‘escape from the Balkans’ and ‘re-integration’ into Central and Western Europe.KEYWORDS: Croatian national integration, Croatian state-building, Croatian nation-building, Yugoslavia, dissolution of Yugoslavia